Geo-Congress 2023. selected papers from sessions of Geo-Congress 2023, March 26 - 29, 2023, Los Angeles, California - Rathje, Ellen M.; Montoya, Brina; Wayne, Mark H. (GSP (Series) ;, 2023)
The sixth volume of six Geotechnical Special Publications (GSPs) contains 67 peer-reviewed papers on geotechnical systems presented at Geo-Congress 2023. Topics include: embankments, dams, and slopes; geotechnical challenges in major projects; pavements; ports and harbors; spatially distributed infrastructure; Twenty Eight by 28; underground engineering and construction; and unsaturated soils.